A randomised trial of hip protector use by frail older women living in their own homes. Issue 2 (1st June 2003) - Cameron, I D; Cumming, R G; Kurrle, S E; Quine, S; Lockwood, K; Salkeld, G; Finnegan, T
Abstract : Objectives: To investigate the efficacy and effectiveness of hip protectors in frail community living older women. Design: Randomised controlled trial. Setting: Aged care health services in New South Wales, Australia. Patients: 600 women 74 years of age or more (mean age 83 years), who had two or more falls or one fall requiring hospital admission in the previous year, and who lived in their own homes. Intervention: Use of hip protectors. Main outcome measures: Adherence with use of hip protectors, falls, incidence of hip fracture, and adverse effects of use of hip protectors. Results: Adherence was approximately 53% over the duration of the study and hip protectors were worn at the time of 51% of falls in the intervention group. The risk of hip fracture when falling while wearing hip protectors, compared with a fall with no hip protectors in place, was significantly reduced (relative risk (RR) 0.23, 95% confidence interval (CI) 0.08 to 0.67). On an intention to treat analysis, 21 and 22 hip fractures occurred in the intervention and control groups respectively (adjusted RR 0.92, 95% CI 0.51 to 1.68). Three users of hip protectors sustained a hip fracture while wearing properly applied protectors, while 16 hip protector users (5%) developed minor local complications. Conclusions: Hip protectors prevent hip fractures in community dwelling older women if worn at the time of a fall. The overall effectiveness of hip protectors was not established in this study, because of incomplete adherence with use of the protectors, and limited statistical power.